2010
DOI: 10.1556/jep.8.2010.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Marital satisfaction and the impact of children in collectivist cultures: A meta-analysis

Abstract: Abstract. Many studies have established that the presence and number of children have a negative impact on marital satisfaction. Those that maintain an evolutionary perspective may find this result surprising. It is argued that a couple that has successfully reproduced together ought to have heightened satisfaction. The majority of studies confirming this negative impact children bring have been on samples of participants from individualist cultures such as the United States and Canada. This severely limits th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…stage caused stress in the couple resulting in reduced sexual satisfaction (28). A meta-analytical study by Dillon and Beechler also reflected that the number of children had a negative effect on marital satisfaction (29). Evidence showed that marital satisfaction in middle-aged couples who had high level of nontangible supports from adult children was high (30).…”
Section: Discussionmentioning
confidence: 99%
“…stage caused stress in the couple resulting in reduced sexual satisfaction (28). A meta-analytical study by Dillon and Beechler also reflected that the number of children had a negative effect on marital satisfaction (29). Evidence showed that marital satisfaction in middle-aged couples who had high level of nontangible supports from adult children was high (30).…”
Section: Discussionmentioning
confidence: 99%
“…A positive relationship has been observed between the number of children and marital satisfaction in countries with a weak social welfare, in which older children and adolescents are considered the main financial supporters of their family, especially in old age. In these countries, most families live with their extended members, and other family members help the mother raise their children (13,46). In the modern age, however, such arrangements are almost nonexistent in most communities, especially in urban ones.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the universal importance of positive relationships for our health and well-being [65] cross-cultural data on associations within what is associated with a satisfactory relationship is lacking. To date, a majority of research on the predictors of marital satisfaction has been largely examined within the Western, educated, industrialized, rich, and democratic (WEIRD) world [12,31,38,66] which leaves a gap in the literature related to the generalizability of previous findings on predictors of marital satisfaction.…”
Section: Methodology Of the Studymentioning
confidence: 99%
“…Models that aim to explain the impact of number of children on marital satisfaction include role conflict, restriction of freedom, sexual dissatisfaction, and financial costs associated with having children [37]. Furthermore, Dillon and Beechler [38] conducted a meta-analysis that aggregated the findings on the association between number of children and marital satisfaction in 15 collectivistic cultures, and they also found a negative correlation between these variables. In contrast, based on a sample of close to 7000 American respondents, Nelson and colleagues [39] found that couples with children reported higher levels of happiness, meaning of life, and positive emotions compared to those who did not have children.…”
Section: Number Of Childrenmentioning
confidence: 99%